2015
DOI: 10.1038/ncb3230
|View full text |Cite
|
Sign up to set email alerts
|

ATM functions at the peroxisome to induce pexophagy in response to ROS

Abstract: Peroxisomes are highly metabolic, autonomously replicating organelles that generate ROS as a by product of fatty acid β-oxidation. Consequently, cells must maintain peroxisome homeostasis, or risk pathologies associated with too few peroxisomes, such as peroxisome biogenesis disorders, or too many peroxisomes, inducing oxidative damage and promoting diseases such as cancer. We report that the PEX5 peroxisome import receptor binds ataxia-telangiectasia mutated (ATM) and localizes this kinase to the peroxisome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
366
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 369 publications
(378 citation statements)
references
References 62 publications
8
366
2
2
Order By: Relevance
“…While a number of cytoplasmic proteins have been shown to be phosphorylated after ATM activation by DNA-damaging agents (28,(42)(43)(44)(45)(46)(47)(48)(49)(50), the only direct evidence for activation in the cytoplasm has only recently been demonstrated (10). In that report, they show that ATM is localized to the peroxisome in agreement with earlier observations (11).…”
Section: (Supplementalsupporting
confidence: 82%
See 1 more Smart Citation
“…While a number of cytoplasmic proteins have been shown to be phosphorylated after ATM activation by DNA-damaging agents (28,(42)(43)(44)(45)(46)(47)(48)(49)(50), the only direct evidence for activation in the cytoplasm has only recently been demonstrated (10). In that report, they show that ATM is localized to the peroxisome in agreement with earlier observations (11).…”
Section: (Supplementalsupporting
confidence: 82%
“…In this case the active form of ATM is not a monomer but rather a disulfide-linked, covalent dimer, and the suite of downstream substrates appears to be more limited than that activated by DNA double strand breaks (5). More recently, it has been reported that the peroxisome import receptor protein, PEX5, binds ATM and localizes it to peroxisomes (10). ATM had previously been localized to this organelle (11).…”
mentioning
confidence: 99%
“…Catalase activity is lower in ATM-deficient human cells compared to normal controls (71) and in ATM−/− mice where the deficit was reported specifically in the cerebellum (72), an important detail given the Purkinje cell specificity of the A-T disorder in humans. The ATM protein has also been reported to be associated with peroxisomes (52, 73), the location of catalase activity in human cells, which is perhaps relevant to the overall deficit in catalase function in cells lacking ATM.…”
Section: Discussionmentioning
confidence: 99%
“…While some of these also include DNA strand breaks, other suggestions involve oxidative stress, mitochondrial dysfunction, and altered ATM cytoplasmic (non-DNA damage) functions (Eaton et al 2007;Guo et al 2010;ValentinVega et al 2012;Zhang et al 2015;Fang et al 2016). Currently, the important etiologic agents and the actual basis for cell loss that results in neurodegeneration remain uncertain.…”
Section: A-t and Atm: A Paradigm For Dna Damage-related Neurodegeneramentioning
confidence: 99%